The Relationship Between Dynamic Balance Ability and Shoulder Pain in High School Baseball Pitchers. (May 2022) - Nakase, Kurumi; Shitara, Hitoshi; Tajika, Tsuyoshi; Kuboi, Takuro; Ichinose, Tsuyoshi; Sasaki, Tsuyoshi; Hamano, Noritaka; Endo, Fumitaka; Kamiyama, Masataka; Miyamoto, Ryosuke; Yamamoto, Atsushi; Kobayashi, Tsutomu; et al.
Background: Dynamic balance is essential for pitching motion because pitching kinematics requires whole body coordination. The Star Excursion Balance Test (SEBT) and the Y balance test (YBT) evaluate dynamic balance quantitatively. There are some reports that investigated the relationship between SEBT/YBT and pain in upper and lower extremities, but there is no study among high school baseball pitchers. Hypothesis: Dynamic balance deficiency is associated with shoulder pain among high school baseball pitchers. Study Design: Cross-sectional study. Level of Evidence: Level 4. Methods: A total of 259 male high school pitchers who participated in the preseason medical checkups were included in the study. YBT was used to measure their dynamic balance. The participants completed a questionnaire which asked if they were currently experiencing shoulder pain. Results: Twenty-two pitchers had shoulder pain during the preseason medical checkups. In the YBT, the posterolateral balance while standing with the axis leg as well as the posteromedial and posterolateral balance while standing with the step leg were significantly lower in the pain group than in the nonpain group ( P = 0.05, 0.04, and 0.001, respectively). A logistic regression analysis showed that posterolateral balance when standing with the step leg was an independent risk factor for current shoulder pain ( P = 0.04, odds ratio 0.942, 95% CI 0.892-0.996). Conclusion: The dynamic balance of high school baseball pitchers with shoulder pain was lower than that of participants without shoulder pain. In particular, posterolateral direction with the step leg standing was significantly related to shoulder pain. Clinical Relevance: Among high school baseball pitchers, decreased dynamic balance was related to current shoulder pain. YBT maybe recommended in preseason medical checkups for high school baseball pitchers.